Scaling up a Project Portfolio Selection Technique by using Multiobjective Genetic Optimization - Barros, Márcio de Oliveira; Costa, Hélio; Figueiredo, Fábio Vitorino; Rocha, Ana Regina Cavalcanti (iSys - Brazilian Journal of Information Systems, 2014)
This paper proposes a multiobjective heuristic search approach to support a project portfolio selection technique on scenarios with a large number of candidate projects. The original formulation for the technique requires analyzing all combinations of the candidate projects, which turns to be unfeasible when more than a few alternatives are available. We have used a multiobjective genetic algorithm to partially explore the search space of project combinations and select the most effective ones. We present an experimental study based on four real-world project selection problems that compares the results found by the genetic algorithm to those yielded by a non-systematic search procedure (random search). A second experimental study evaluates the best parameter settings to perform the heuristic search. Experimental results show evidence that the project selection technique can be used in large-scale scenarios and that the genetic algorithm presents better results than simpler search strategies.